Synthesis, Crystal Structural Characterization and Biological Properties of Thiosemicarbazones of Schiff Bases Derived from 4-Acyl-2-pyrazoline-5-one - Arjunsinh Rana; Nayan Parekh; Harish Dabhi; Dipak Bhoi; Niraj Kumari (E-Journal of Chemistry)
A novel synthesis, single crystal and biological activity of 4-acylthiosemicarbazone-3-methyl-1-(4`-methylphenyl)-2-pyrazolin-5-one by condensation of 4-acyl-3-methyl-1-(4`-methylphenyl)-2-pyrazolin-5-one with thiosemicarbazide was carried out. The compounds were characterized on the basis of elemental analysis, IR, 1H NMR, Mass, DSC and 13C NMR spectral data. The compounds were tested for their antibacterial activity against various gram +ve and -ve bacteria. The results were compared with the marketed drugs. The crystal structure was determined by single x-ray diffraction. 4-Acetyl thiosemicarbazone-3-methyl-1-(4`-methylphenyl)-2-pyrazolin-5-one(AcPTMP-ths) crystallizes in the monoclinic system, space group P21/n with a=6.0828(7)Å, b=29.547(4)Å, c=7.9101(15)Å, α=90°, γ=95.602(15)°, γ=90°, V=1414.9(4) Å3, Z=4, Dc=1.429 mg/m3 and 4-Propionylthiosemicarbazone-3-methyl-1-(4`-methylphenyl)-2-pyrazolin-5-one (PropPTMP-ths) crystallizes in the monoclinic system, space group P21/c with a=13.5622(10)Å, b=13.3671(12)Å, c=22.151(2)Å, α=90°, β=93.13(7)°, γ=90°, V=4010.1(6) Å3, Z=8, Dc=1.310 mg/m3. The compounds were screened for antibacterial properties and exhibited potential activity.